Prenatal Diagnosis and Pregnancy Termination in Jewish and Muslim Women with a Deaf Child in Israel - Aliza Amiel; Wasef Na'amnih; Mahdi Tarabeih (MDPI AG, 2023)
Deafness is the most common sensory disability in humans, influencing all aspects of life, However, early diagnosis of hearing impairment and initiating the rehabilitation process are of great importance to enable the development of language and communication as soon as possible. We examined the differences in attitudes towards performing prenatal invasive tests and pregnancy terminations in Jewish and Muslim women in Israel due to deafness. Overall, 953 Israeli women, aged 18-46 years with a mean age of 32.0 (SD = 7.12), were enrolled. Of those, 68.7% were city dwellers and 31.3% were village dwellers, and 60.2% were Muslim women and 39.8% were Jewish women. All participants had a child with a hearing impairment or deafness. The group with no genetic hearing loss performed more prenatal invasive tests and pregnancy terminations than those with genetic hearing loss in both ethnic groups. Jewish women performed more invasive prenatal tests and, consequently, a pregnancy termination. Secular Jewish women more frequently underwent pregnancy terminations due to fetal deafness. Further genetic counseling and information concerning IVF and PGD procedures should be provided to the Muslim population.